Bone morphogenetic protein‐2 incorporated calcium phosphate graft promotes peri‐implant bone defect healing in dogs: A pilot study. Issue 5 (7th July 2022) - Uijlenbroek, Henri J. J.; Lin, Xingnan; Liu, Tie; Zheng, Yuanna; Wismeijer, Daniel; Liu, Yuelian
Abstract: Objectives: The evaluation of three different drug delivery modes of bone morphogenetic protein‐2 (BMP‐2) in healing peri‐implant bone defects in beagle dogs. BMP‐2 was incorporated in or onto calcium phosphate (CaP) granules in various ways: (i) directly on the outer layer of granules CaP: as an adsorbed depot; (ii) during the entire precipitation process of CaP: an internally incorporated depot; or (iii) during the biomimetic coating precipitation of BMP‐2 on the surface of CaP granules: as a coating incorporated depot. Material and Methods: After extraction of the lower molars and wound healing in 6 male beagle dogs, 36 implants were placed ( n  = 6 animal per group). Peri‐implant bone defects were induced. The following treatment groups were evaluated: no treatment; air abrasive surface cleaning (SC) using hydroxyapatite; SC and the subsequent filling of the defect with CaP without BMP‐2; SC plus the subsequent filling of the defect with CaP adsorbed BMP‐2; SC plus the subsequent filling of the defect with CaP internally incorporated BMP‐2; SC plus the subsequent filling of the defect with CaP coating incorporated BMP‐2. Histological and histomorphometric analyses were carried out to quantify and compare the changes in bone tissue surrounding the treated implants. Results: In Group 1 with no treatment, four implants were lost. Group 5 with the SC and the subsequent filling of the defect with internally incorporated BMP‐2 biomimetically prepared CaP (BioCaP), whereby the BMP‐2 is incorporated in the entire volume of all BioCaP particles, showed overall the best results to regenerate bone around the implants. Conclusion: This study concluded that the group treated with SC plus the subsequent filling of the defect with CaP BMP‐2 internally incorporated BMP‐2, whereby BMP‐2 has been incorporated in the entire volume of all CaP particles, showed overall the best results when aiming to regenerate bone around the implants.